Reflections on Dependence and the Rhetoric of Development in Africa - OKAFOR, Uzodinma C.; EZE, Jeremiah N.; EZEAMU, Emmanuel O. (Socialscientia: Journal of Social Sciences and Humanities, 2022)
The experiences of colonialism have thwarted and betrayed the value of sovereignty across African states. This has made the process of development relatively difficult and unattractive among most states in Africa. As such, Africa was unavoidably traded in deceit giving room for the dependence of African states on the western metropoles. Objectively, there is a likelihood that Africa has been fed with wrong development pills which has continued to make Africa helpless without the west. The study adopted qualitative design utilizing documentary evidence as the method of data collection. Deductive method of analysis was also considered while dependency and neo-colonial theories of the state provide the framework of analysis. The study discovered that the development of African states is placed on autopilot by both the western and indigenous capitalists leaving the states shattered and exposed for further exploitation. The resultant effect is nothing but continuous dependence on the west and China for survival. As such, this paper calls for an investment in human capital (internal potentials) with serious demand for results and expansion.